Stratification of Intermediate-risk Non-muscle-invasive Bladder Cancer Patients: Implications for Adjuvant Therapies - Soria, Francesco; D'Andrea, David; Abufaraj, Mohammad; Moschini, Marco; Giordano, Andrea; Gust, Kilian M; Karakiewicz, Pierre I; Babjuk, Marek; Gontero, Paolo; Shariat, Shahrokh F (European urology focus, 2021)
BACKGROUND: There is an urgent need to provide a risk-stratification tool for intermediate-risk non-muscle-invasive bladder cancer (NMIBC), especially at the time of bacillus Calmette-Guerin (BCG) shortage. OBJECTIVE: To assess whether patients with intermediate-risk NMIBC can be stratified into different risk groups, thereby providing a practical tool for the selection of the optimal adjuvant therapy, based on the individualized risk of disease progression. DESIGN, SETTING, AND PARTICIPANTS: This was a retrospective analysis of 636 patients with intermediate-risk NMIBC. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: A multivariable Cox-regression model was built to evaluate the impact of each variable on recurrence and progression to muscle-invasive disease. A Cox-based nomogram to predict patient-specific probability of disease progression was performed, and the decision curve analysis (DCA) was used to evaluate its clinical benefit. RESULTS AND LIMITATIONS: Within a median follow-up of 92 mo (interquartile range 56-118), disease recurrence and progression occurred in 346 (54%) and 91 (14%) patients, respectively. On multivariable analysis, age, early recurrence (<12 mo), and tumor size≥3cm were found to be independent predictors of progression. The Harrell C-index of the model for the prediction of progression was 0.75 and exceeded that of the model proposed by the International Bladder Consultation Group. DCA showed superior net benefits for the nomogram compared with the strategies of treating all/none and previous predictive models. Limitations are inherent to the retrospective design. CONCLUSIONS: We provided a risk-stratification tool that helps identify individual risk of disease progression in patients with intermediate-risk NMIBC. This tool outperforms standard strategies in the threshold probability range of interest and could help select the optimal intravesical therapy regimen based on the individual risk of disease progression. PATIENT SUMMARY: In this study, we provided a practical tool for risk stratification in patients with intermediate-risk non-muscle-invasive bladder cancer. This tool may help select the most appropriate adjuvant therapy (either bacillus Calmette-Guerin [BCG] or chemotherapy) based on patient and tumor characteristics, thus making a step forward toward the era of personalized medicine.
Keywords: Progression; Bacillus Calmette-Guerin; Neoplasm Recurrence, Local; Risk stratification; Adjuvants, Immunologic; lidé; Intermediate risk; retrospektivní studie; Urinary Bladder Neoplasms; progrese nemoci; nádory močového měchýře; Disease Progression; lokální recidiva nádoru; Non–muscle-invasive bladder cancer; BCG vakcína; BCG Vaccine; Retrospective Studies; adjuvancia imunologická; Humans